Biomechanical gait analysis based on a worldwide network of research and clinical partner - Ferber, R. (International Calgary Running Symposium, August 14-17, 2014, 2014)
Biomechanical gait analysis is one of the most ubiquitous research methods for analyzing sport performance and assessing mobility. However, many laboratories function in isolation, thus limiting the scope of research that can be done. We believe that in order to advance biomechanics research, new approaches must be developed that promotes collaboration and sharing of data. To this end, we have assembled a network of 35 research and clinical partners, and a comprehensive database of 3-dimensional (3D) gait data known as FeBE (Fetch By Email). Our research partners consist of university-level gait labs and our clinic partners are primarily physiotherapists. FeBE is designed to support hypothesis-driven research and currently contains over 2500 unique subjects. It is growing every day as new data are added and, to our knowledge, it is the largest relational database of gait biomechanics and clinical data in the world. The overarching purpose of our efforts is to create an open-access research database, which supports hypothesis-driven inquiry. Moreover, the Natural Sciences & Engineering Research Council (NSERC) has recently recognized our work with an Accelerator Award. This award is only given to "a small group of researchers to explore high-risk, novel or potentially transformative concepts and lines of inquiry, and are likely to have impact by contributing to groundbreaking advances in the area." We invite the scientific community to join our research efforts and become a research partner within our network.